The Corona Pandemic and its Direct Role in Reducing the Volume of Tax Revenue Subject to the Provisions of the Iraqi Income Tax Law No. 113 of 1982, the Effective Amendment - Abdullah, Meena; Almayahi, Ammar (Journal of Legal Sciences, 2023)
The Corona pandemic is a virus that affects both humans and animals that was discovered in China in (2019) and then spread to the rest of the world in late (2019) And as an attempt to control it, several restrictions were imposed, and these restrictions would paralyze the global economy, including the Iraqi economy, as it resulted in a state of financial and tax stagnation in particular, as Corona affected the volume of tax revenue, causing a severe and noticeable decrease in the volume of revenue in the year (2021). No measures were taken that would restore the balance to the level of tax revenue. No new exemptions were reported, and no new tax bases were taken .